Dysregulation of Respiratory Center Drive (P0.1) and Muscle Strength in Patients With Early Stage Idiopathic Parkinson's Disease - Zhang, Wei; Zhang, Lei; Zhou, Ning; Huang, Enqiang; Li, Qi; Wang, Tongyu; Ma, Chunchao; Li, Bin; Li, Chen; Du, Yanfen; Zhang, Jing; Lei, Xiaofeng; et al. (Frontiers in Neurology, 2019)
Objective: The goal of this study is to evaluate pulmonary function and respiratory center drive in patients with early-stage idiopathic Parkinson's disease (IPD) to facilitate early diagnosis of Parkinson’s Disease (PD). Methods: 43 IPD patients (Hoehn and Yahr scale of 1) and 41 matched healthy individuals (e.g. age, sex, height, weight, BMI) were enrolled in this study. Motor status was evaluated using the Movement Disorders Society-Unified PD Rating Scale (MDS-UPDRS). Pulmonary function and respiratory center drive were measured using pulmonary function tests (PFT). All IPD patients were also subjected to a series of neuropsychological tests, including Non-Motor Symptoms Questionnaire (NMSQ), REM Sleep Behavior Disorder Screening Questionnaire (RBDSQ), Beck Depression Inventory (BDI) and Mini Mental State Examination (MMSE). Results: IPD patients and healthy individuals have similar forced vital capacity (FVC), forced expiratory volume in 1s (FEV1), forced expiratory volume in 1s/forced vital capacity (FEV1/FVC), peak expiratory flow (PEF) and carbon monoxide diffusion capacity (DLCOcSB). Reduced respiratory muscle strength, maximal inspiratory pressure (PImax) and maximal expiratory pressure (PEmax) was seen in IPD patients (p=0.000 and p=0.002, respectively). Importantly, the airway occlusion pressure after 0.1 second (P0.1) and respiratory center output were notably higher in IPD patients (p=0.000) with a remarkable separation of measured values compared to healthy controls. Conclusion: Our findings suggest that abnormal pulmonary function is present in early stage IPD patients as evidenced by significant changes in PImax, PEmax and P0.1. Most importantly, P0.1 may have the potential to assist with the identification of IPD in the early stage.